2012
DOI: 10.1038/bjc.2012.299
|View full text |Cite
|
Sign up to set email alerts
|

Cervical human papillomavirus and HIV infection in women of child-bearing age in Abidjan, Côte d’Ivoire, 2010

Abstract: Background: We sought to document the association of Human immunodeficiency Virus (HIV) infection and immunodeficiency with oncogenic Human Papillomavirus (HPV) infection in women with no cervical neoplastic lesions identified through a cervical cancer screening programme in Côte d'Ivoire. Methods: A consecutive sample of women stratified on their HIV status and attending the national blood donor clinic or the closest HIV clinic was recruited during a cervical cancer sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
4
30
3
Order By: Relevance
“…This test uses biotinylated PGMY primers to amplify a 450-bp fragment within the polymorphic L1 region of the HPV genome and allows for the identification of 37 anogenital HPV types [6, 11, 16, 18, 26, 31, 33, 35, 39, 40, 42, 45, 51, 52, 53, 54, 55, 56, 58, 59, 61, 62, 64, 66, 67, 68, 69, 70, 71, 72, 73 (MM9), 81, 82 (MM4), 83 (MM7), 84 (MM8), IS39, and CP6108]. The HPV52 detected by the LA test could represent concurrently present HPV33, HPV35 and HPV58, because the probe for HPV52 is a mixed probe that cross-reacts with these 3 types [16]. The LA HPV test also amplifies a 265-bp region of the human β -globin gene that serves as an internal control for DNA extraction and amplification.…”
Section: Methodsmentioning
confidence: 99%
“…This test uses biotinylated PGMY primers to amplify a 450-bp fragment within the polymorphic L1 region of the HPV genome and allows for the identification of 37 anogenital HPV types [6, 11, 16, 18, 26, 31, 33, 35, 39, 40, 42, 45, 51, 52, 53, 54, 55, 56, 58, 59, 61, 62, 64, 66, 67, 68, 69, 70, 71, 72, 73 (MM9), 81, 82 (MM4), 83 (MM7), 84 (MM8), IS39, and CP6108]. The HPV52 detected by the LA test could represent concurrently present HPV33, HPV35 and HPV58, because the probe for HPV52 is a mixed probe that cross-reacts with these 3 types [16]. The LA HPV test also amplifies a 265-bp region of the human β -globin gene that serves as an internal control for DNA extraction and amplification.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in a meta-analysis of 1 million women with normal cytological findings published in 2010, Bruni et al reported a prevalence of 24% in sub-Saharan Africa [17]. This prevalence is also low compared with the prevalence found in other West African countries, with 33.2% in Benin, 24.3% in Burkina Faso and 50.3% in Côte d'Ivoire [5,9,18]. This difference could be explained by many factors such as the laboratory technique used, the age and HIV status of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Since no data on HPV infection were available in the general population in Togo, the sample size calculation was based on the following assumptions: an expected prevalence of HPV infection of 30% based on estimates in a population of HIV-negative women of child-bearing age of 33% in Côte d'Ivoire [5], country of West Africa, with a precision of 6%, a significance level set at 5% and a non-response rate of 10%; the minimum sample size was estimated at 246 participants.…”
Section: Sample Size and Participantsmentioning
confidence: 99%
See 2 more Smart Citations